Acceptability, feasibility and costs of universal offer of rapid point of care testing for HIV in an acute admissions unit: results of the RAPID project1. (28th August 2013) - Burns, F; Edwards, SG; Woods, J; Haidari, G; Calderon, Y; Leider, J; Morris, S; Tobin, R; Cartledge, J; Brown, M
Abstract : Objectives: UK guidance recommends that acute medical admissions are offered an HIV test. Our aim was to determine whether a dedicated staff member using a multimedia tool, a model found effective in the USA, is an acceptable, feasible, and cost‐effective model when translated to a UK setting. Methods: Over 4 months in 2010, a health advisor (HA) approached 19–65‐year‐olds at a central London acute medical admissions unit and offered a rapid HIV point of care test (POCT) with the aid of an educational video. Feasibility and acceptability were assessed through surveys and uptake rates. Costs per case of HIV infection identified were established. Results: Of the 606 eligible people admitted during the pilot, 324 (53.5%) could not be approached or were individuals for whom testing was deemed inappropriate. In total, 23.0% of eligible admissions had an HIV POCT. Of the patients who watched the video and had not recently been tested for HIV, 93.6% (131 of 140) agreed to an HIV test; four further patients had an HIV test but did not watch the video. Three tests (2.2%; three of 135) were reactive and all were confirmed HIV positive on laboratory testing. HIV testing in this setting was felt to be appropriate by 97.5% of individuals. The cost per patient was £21, and the cost per case of HIV identified was £1083. Conclusions: Universal POCT HIV testing in an acute medical setting, facilitated by an educational video and dedicated staff, appears acceptable, feasible, effective, and low cost. These findings support the recommendation of HIV testing for all medical admissions in high‐prevalence settings, although with this model a significant proportion remained untested.